Prevalence of hypovitaminosis D among children and adolescents of Kabul: a descriptive cross-sectional study - Mohammad Sharif Sediqi; Abdul Rasheed Mansoor; Mohmand Mangal (BMC, 2023)
Abstract Background Vitamin D is one of the most important fat-soluble vitamins necessary for normal growth and development of the human body. According to a study done in Kabul shows that economic, racial, and social concerns are thought to be the main impediments to receiving appropriate amounts of this vitamin through dietary sources in countries like Afghanistan. Hypovitaminosis D, on the other hand, is now recognized as a pandemic in both industrialized and developing countries. Methods To find out how common hypovitaminosis D is in children aged one month to eighteen years in afghan children Kabul, Afghanistan. Vitamin D deficiency and insufficiency are defined as serum levels of less than 20 ng/mL and 20 to 30 ng/mL, respectively. Children aged between 1 month to 18 years attending our hospital, AMC (Ariana Medical Complex) for health examination were checked for their 25-hydroxyvitamin D [25(OH)D]. Age, gender and address were recorded. 25(OH)D were determined using immunoassay auto analyzers. According to their serum 25(OH)D, the 25(OH)D were categorized into five categories: sufficiency: ≥ 30-100 ng/mL; insufficiency: ≥ 20-29 ng/mL; deficiency: < 20 ng/mL; severe deficiency: < 10 ng/mL; and intoxication: > 150 ng/mL. Participants who were intoxicated with vitamin D were excluded from the study. Results A total of 4008 children aged 1 month to 18 years participated in this cross-sectional study. Hypovitaminosis D was found to be prevalent in 62.5 percent of the population. When compared to boys, female children were 1.2 times more likely to be vitamin D deficient. When compared to children of illiterate women, the odds of hypovitaminosis D were 1.4, 1.9, and 5.8 times lower in children with mothers educated up to primary school, graduation, and post-graduate. The average vitamin D level was 23 ng/mL, with a median of 15 ng/mL and maximum and minimum values of 135 ng/mL and 3 ng/mL, respectively. In all, 2500 (62.5%) of the children had low levels of vitamin D in their serum. Only 400 (16%) of the patients were sufficient, whereas 917 (36.7%) were severely deficient, 733 (29.3%) were deficient, and 450 (18%) were insufficient. With a female to male ratio of 1.2:1, the majority of those, 1335 (53.4%), were females and 1165 (46.6%) were males. Patients were 8.14 years old on average, with a median age of 7 years. The majority of the patients, 2152 (86.1%), were urban, while 348 (13.9%) were rural. Conclusion The prevalence of hypovitaminosis D was very high in Afghan children. Female sex, higher socio economic status, higher educational status of the mother and living at urban areas were the factors with strong positive association with hypovitaminosis D.